FACTORS THAT INFLUENCE WAQIF INTENTION ON CASH WAQF AND WAQF THROUGH MONEY - Kameswari, Ika; Beik, Irfan Syauqi; Asnawi, Yudha Heryawan (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2023)
Cash waqf and waqf through money as one of form of alms giving the reward of jariyah, have large gap between potential and realization. Therefore, this research aims to describe respondent’s characteristics and analyze factors that might be influenced waqifs’ intention to do cash waqf or waqf through money particularly through berkahwakaf.id. The method used in this study were descriptive and logistic regression analysis. This study involved 186 respondents from berkahwakaf.id and non-berkahwakaf.id waqifs. The result show that the character of respondent was balanced between male and female, dominated by age range 25-57 years old, dominated with minimum undergraduate education level, private and government employee with average income more than Rp 5 million. Data analysis result show that the waqif’s intention to do cash waqf and waqf through money affected by subjective norms, promotion and education level have asignificant positive affect and income level has a significant negative effect.